The phenotypic characteristics and relational database for Vietnamese native pig populations. (7th July 2020) - Ishihara, Shinya; Yamasaki, Fukuhiro; Ninh, Pham Hai; Dinh, Nguyen Cong; Arakawa, Aisaku; Taniguchi, Masaaki; Cuc, Ngo Thi Kim; Mikawa, Satoshi; Takeya, Masaru; Kikuchi, Kazuhiro
Abstract: Although there are a number of Vietnamese native pig (VnP) populations, some are on the verge of extinction, and therefore adequate management and conservation are necessary. In this study, we conducted a field survey of VnP populations and analyzed interrelationships among their characteristics. We also established a relational database for management of field data on these populations. For data collection, we conducted interviews with farmers and visual inspection of 32 VnP populations in 22 provinces of Vietnam, as well as taking photographs of individual animals. Data on the characteristics of VnP populations were subjected to multiple correspondence analysis (MCA). For establishment of the database, normalization and table partitioning were performed to eliminate redundancy and ensure consistency of the collected data items. Passport data, characteristics data, and image data were collected from a total of 1, 918 VnPs and entered as a normalized table. Upon MCA, most of the populations were not separated from each other, but the Mong Cai, O Lam, and Chu Prong populations were separated from the other populations. Thus, we have constructed a relational database from comprehensive information on the characteristics of VnP populations.